The clinical course and standard therapy of systemic lupus erythematosus in the Russian Federation - E. L. Nasonov; S. K. Solovyev; A. M. Lila (Современная ревматология, 2016)
Data on the clinical course and treatment of such as the severe disease systemic lupus erythematosus (SLE), are virtually lacking in Russia.Objective: to evaluate the clinical presentations of the disease and its treatment in adult patients with active SLE in the cities of three post-Soviet countries (Russia, Ukraine, and Kazakhstan) in the ESSENCE study.Patients and methods. This paper concerns Russian patients. The data of clinical cases of 232 patients who were followed up in 6 centers (Moscow, Saint Petersburg, Voronezh, Yekaterinburg, Kursk, and Yaroslavl) were studied. The demographic and clinical characteristics of the patients, SLE activity, laboratory and instrumental findings, treatment, and consumed healthcare resources were assessed.Results. The demographic characteristics of patients with SLE were generally comparable to those in other international studies. However, the Russian patients were 4–10 years younger and their SLE duration was 3–7 shorter; the majority of patients were noted to have a severe course of the disease. The level of SLE activity was higher in the patients of our study. There were frequent hospitalizations and unplanned visits to a physician because of exacerbations. The Russian patients who had repeatedly sought medical advice had obvious and severe SLE complications. The disease remained with great probability undiagnosed or misdiagnosed in a sufficiently large number of patients. There were pitfalls in the treatment of SLE: less than half of the patients received antimalarial drugs; nearly 100% took glucocorticoids; nonsteroidal anti-inflammatory drugs were used rarely. The ESSENCE study can form a view of the clinical picture of SLE in Russia. These findings may help to plan healthcare resources in our country.